A new non-parasemionotiform order of the Halecomorphi (Neopterygii, Actinopterygii) from the Middle Triassic of Tethys. (4th March 2017) - Zuoyu, Sun; Tintori, Andrea; Yaozhong, Xu; Lombardo, Cristina; Peigang, Ni; Dayong, Jiang
Abstract : The halecomorph fish Panxianichthys imparilis, from the Pelsonian (Anisian, Middle Triassic) of Panxian County, Guizhou Province, South China, was recently described in brief. Here we present a thorough revision of this taxon based on 22 specimens, which allows a much better understanding of its anatomy and, consequently, its phylogenetic relationships. Newly recognized anatomical features include a flat quadratojugal, a symplectic articulating with the lower jaw ventral to the quadrate articulation, five infraorbitals, up to three suborbitals, and a large tail body lobe. Panxianichthys represents the oldest known non-parasemionotiform halecomorph and has a crescent-shaped preopercle and a maxillary branch of infraorbital sensory canal, but it is excluded from the 'Ionoscopiformes–Amiiformes' clade mainly by the presence of a quadratojugal, a dermosphenotic hinged to the side of the skull roof with a smooth innerorbital flange bearing no sensory canal, and a symplectic articulation much more ventral than that of the quadrate. A comparison with other Triassic non-parasemionotiform halecomorphs, together with the phylogenetic analysis, supports the erection of a new halecomorph order, Panxianichthyiformes, which is the sister group to the post-Triassic 'Ionoscopiformes–Amiiformes' clade. In addition, Robustichthys, also from the Anisian and previously ascribed to Ionoscopiformes, is recognized here as a new stem-group Ginglymodi. http://zoobank.org/urn:lsid:zoobank.org:pub:5594E962-985F-466D-AC52-2E9A5AC07787